Manajemen Filantropi Islam untuk Pendidikan Studi Program Jogja Cerdas Baznas Kota Yogyakarta - Khamim Tohari; Imam Machali (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2022)
This research described the management of Islamic philanthropic funds for the Jogja Smart program at BAZNAS Yogyakarta City. The Jogja Smart program aimed to improve the quality and quantity of underprivileged students from TK/RA to tertiary institutions. For this reason, a good fundraising, management, and program evaluation strategy was needed so that it could be utilized in accordance with its objectives. This research used qualitative research with case study type. Methods of data collection used observation, in-depth interviews and documentation. The results showed that the Islamic Philanthropy Fundraising Strategy consisted of identifying potential donors, using fundraising methods, managing and maintaining donors and monitoring and evaluating fundraising. The management of the Jogja Smart Program was realized in (1) Foster Children Scholarships (2) Community Dhuafa Children Scholarships (3) Al Qur'an Diniyyah Ta'milyyah Madrasas (4) Productive Student Scholarships (5) Smart Villages (6) Mobile Inspiration. The evaluation of the Jogja Smart program used the CIPP evaluation model. The evaluation results on the components of context, input, process and product were in the good category. The Jogja Smart program provided positive outputs and benefits for the underprivileged in the city of Yogyakarta. However, new innovations were needed in the future to make this program more useful.